2020
DOI: 10.3389/fnut.2020.576133
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Non-nutritional Composition of Human Milk Is Modulated by Maternal, Infant, and Methodological Factors

Abstract: Human milk (HM) is dynamic and shows a high inter- and intra-individual variability. To characterize HM with precision, it is necessary to understand the factors that modulate its composition. The objective of this narrative review is to summarize the maternal, infant and methodological factors that affect HM composition. We searched SCOPUS and PubMed databases for articles related to factors that are known to or could potentially influence HM composition and volume across lactation periods. Our comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
99
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 262 publications
(317 reference statements)
1
99
0
2
Order By: Relevance
“…One of the supplementary proteins that is effective in improving weight gain and head circumference growth, height and probably the immune system (4). The American Academy of Pediatrics (AAP) and the WHO strongly recommend breastfeeding for preterm and premature infants, but it doesn't meet newborns protein requirements (3); so it is necessary to enrich breast milk to meet the needs of the VLBW infants. A common strategy for enriching breast milk is the addition of fortified milk supplement (FMS) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the supplementary proteins that is effective in improving weight gain and head circumference growth, height and probably the immune system (4). The American Academy of Pediatrics (AAP) and the WHO strongly recommend breastfeeding for preterm and premature infants, but it doesn't meet newborns protein requirements (3); so it is necessary to enrich breast milk to meet the needs of the VLBW infants. A common strategy for enriching breast milk is the addition of fortified milk supplement (FMS) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…©Copyright 2021 by Erciyes University Faculty of Medicine -Available online at: www.erciyesmedj.comThis study was performed with the assumption that high-dose supplementary proteins improve weight gain in preterm infants compared to moderate doses or absence of the supplementary protein. Miller et al showed that the group receiving protein (4.2 gr/kg/d) showed a higher weight gain compared to the group receiving the protein (3.6 gr/kg/d)(3). Also, the results of Rochow & Biasin's study showed similar effects of high-dose protein supplement in increasing the weight gain(6,7).…”
mentioning
confidence: 97%
“…The chemical composition of human milk changes from colostrum to late lactation, and varies within feeds, diurnally, and between mothers ( 1 ), being influenced by both maternal and environmental factors and showing high inter- and intra-individual variability ( 3 ). It has been shown that birth weight, gestational age, infant age/stage of lactation has an impact on the composition, but less is known how the maternal factors such as lifestyle (except for the mother’s diet) and socio-demographic factors are affecting the BM composition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that birth weight, gestational age, infant age/stage of lactation has an impact on the composition, but less is known how the maternal factors such as lifestyle (except for the mother’s diet) and socio-demographic factors are affecting the BM composition. Interestingly, the socioeconomic status and geographical location were found to have an impact particularly on the lipid composition of the milk ( 3 ). For example, a more favourable balance between omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) was observed in BM of Swedish women compared with Chinese women ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…lactation and between mothers (6,7). The link between the nutrients and other bioactives in human milk and growth occurs at various levels, from appetite regulation to direct sensing of nutrients by immune cells in the intestine.…”
mentioning
confidence: 99%